Hsu-Nielsen source에 의한 두께 및 용접 방법에 따른 STS316L의 탄성파 특성 - 남기우(Ki-Woo Nam); 이기식(Ki-Sik Lee); 탁영준(Young-Joon Tak); 김공영(Gong-Young Kim) (동력시스템공학회지, 2020)
이 논문은 두께 및 용접 방법에 따르는 스테인리스강의 탄성파 특성을 평가하여, 구조물의 모니터링에 기초 데이터로 활용하고자 한다. 모재는 두께가 다른 1, 5 및 25 mm의 스테인리스강을 사용하였으며, 용접재는 레이저 용접 및 TIG 용접한 두께 6 mm의 스테인리스강을 사용하였다. 탄성파는 Hsu-Neilsen source로 발생시켰다. 검출된 신호는 랩뷰를 활용한 시간-주파수 해석법으로 탄성파 특성을 분석하였다. Hsu-Nielsen source에서 검출한 탄성파는 Labview를 활용한 시간-주파수 해석으로 특성을 분석할 수 있었다. 두께에 따른 탁월주파수 대역은 시험편 두께가 두꺼워질수록 하부 주파수 대역은 증가하고, 상부 주파수 대역은 감소하는 경향을 나타내어, 두께의 영향이 있었다. Hsu-Nielsen source에 의한 탁월주파수는 용접 전력, 용접 속도 및 용접 방법에 영향을 받았다. 레이저용접시험편은 용접 전력 5.5 kW 및 용접 속도 1.5 m/min의 조건에서 분산이 가장 작게 나타났다. Elastic waves are signals that appear as energy releases inside a material. Elastic waves show the behavior inside the material. Elastic wave characteristics of stainless steel according to the thickness and welding method are evaluated and will be used as basic data for monitoring the structure. In this study, elastic wave was generated by Hsu-Nielsen source using different thickness of stainless steel plate. Welding method used two types of TIG welding and laser welding. Elastic waves were detected using the NI PXI SYSTEM, which supports up to eight channels. Elastic waves analyzed by time-frequency analysis using Labview. As the thickness of specimen increases, the lower frequency band increases and the upper frequency band decreases. The elastic waves were affected by the welding method, welding power and welding speed. That is, they were affected by the weld shape. KCI Citation Count: 3